2018
DOI: 10.2298/fil1812177s
|View full text |Cite
|
Sign up to set email alerts
|

Semihypergroups obtained by merging of 0-semigroups with groups

Abstract: We consider the class of 0-semigroups (H,) that are obtained by adding a zero element to a group (G, •) so that for all x, y ∈ G it holds x y 0 ⇒ x y = xy. These semigroups are called 0-extensions of (G, •). We introduce a merging operation that constructs a 0-semihypergroup from a 0-extension of (G, •) by a suitable superposition of the product tables. We characterize a class of 0-simple semihypergroups that are merging of a 0-extension of an elementary Abelian 2-group. Moreover, we prove that in the finite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In [16] the authors found all simple and zero-simple semihypergroups of size 3 , such that the fundamental relation β is not transitive, apart from isomorphisms. This semihypergroups of size 3 were used in [8][9][10][11][12] to characterize the fully simple semihypergroups and the fully zero-simple semihypergroups having all hyperproducts of size ≤ 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In [16] the authors found all simple and zero-simple semihypergroups of size 3 , such that the fundamental relation β is not transitive, apart from isomorphisms. This semihypergroups of size 3 were used in [8][9][10][11][12] to characterize the fully simple semihypergroups and the fully zero-simple semihypergroups having all hyperproducts of size ≤ 2 .…”
Section: Introductionmentioning
confidence: 99%